Hubungan Kompetensi dan Kompensasi dengan Kinerja Pegawai Administrasi di RSUP Ratatotok Buyat - Yoan Gigir; Karel Pandelaki; Arthur E. Mongan (e-CliniC, 2023)
Abstract: Good competency could increase the productivity of an employee. Meanwhile, to obtain qualified employees’ performance the compensation must be well planned, integrated and compre-hensive in order to provide a high motivation to achieve the organization goals. This study aimed to determine the relationship between competency and compensation with work performance of the administrative employees at RSUP Ratatotok Buyat, Minahasa Tenggara, Indonesia. In this study we used quantitative and qualitative methods (mixed method). This study was conducted at RSUP Ratatotok Buyat with a total sample of 50 employees and six informants. Primary data were obtained from questionnaires and interview guidelines, while secondary data were from document reading. The results showed that from 23 (46%) respondents with good competency, there were 16 (32%) with good performance and seven (14%) with fair performance. From 27 (54%) res-pondents with fair competency, there were eight (16%) with good performance and 19 (38%) with fair performance. In conclusion, there were positive relationships between competence as well as compensation with work performance of the administrative employees of RSUP Ratatotok Buyat.Keywords: performance; competence; compensation; administrative employee Abstrak: Kompetensi yang baik dapat meningkatkan produktifitas seorang pekerja. Selain itu untuk memperoleh kualitas kinerja yang baik dari pekerja, perlu adanya kompensasi yang terencana dengan baik, terintegrasi dan komprehensif agar mampu memberikan semangat kerja yang tinggi untuk mencapai tujuan organisasi. Penelitian ini bertujuan untuk mengetahui hubungan kompetensi dan kompensasi dengan kinerja pegawai administrasi di RSUP Ratatotok Buyat. Minahasa Tenggara, Indonesia. Jenis penelitian yaitu kombinasi/campuran kualitatif dan kuantitatif (mixed method). Penelitian ini dilakukan di RSUP Ratatotok Buyat dengan total sampel sebanyak 50 orang dan informan sebanyak enam orang. Data primer diperoleh dengan menggunakan kuisioner dan pedoman wawancara sedangkan data sekunder diperoleh melalui penelusuran dokumen. Hasil penelitian mendapatkan bahwa dari 23 responden (46%) yang memiliki kompe-tensi baik, terdapat 16 (32%) dengan kinerja baik dan tujuh (14%) dengan kinerja cukup. Dari 27 responden (54%) yang memiliki kompetensi cukup, terdapat 8 (16%) dengan kinerja baik dan 19 (38%) dengan kinerja cukup. Simpulan penelitian ini ialah terdapat hubungan positif antara kompetensi dan kompensasi dengan kinerja pegawai adminstrasi di RSUP Ratatotok Buyat.Kata kunci: kinerja; kompetensi; kompensasi; pegawai administrasi